Antioxidant and Antibacterial Activity of Ethanol Extract of Butterfly Leaf (Bauhinia Purpurea L.) with Maceration Extraction Method - Surendro, Yasmeen Nazhifah Amani; Nasution , Muhammad Amin; Lubis, Minda Sari; Pulungan, Anili Fithri (Jurnal Biologi Tropis, 2024)
The butterfly plant (Bauhinia purpurea L.) is a plant widely used in traditional medicine to treat various ailments. The butterfly plant's leaves have medicinal properties. The leaves of butterfly plants contain bioactive chemicals that can be employed as natural antibacterial and antioxidant agents. The purpose of this study was to evaluate the ethanol extract of butterfly leaves' antibacterial and antioxidant properties. Butterfly leaf extract was obtained using a maceration process with 96% ethanol solvent. Antioxidant activity was measured using the DPPH (1,1-diphenyl-2-picryhydrazyl) and FRAP (Ferric Reducing Antioxidant Power) techniques, with ascorbic acid as a comparator. The disc paper diffusion method was used to test the antibacterial activity against Streptococcus mutans bacteria. The DPPH method has an IC50 value of 27.5484 µg/ml with a very strong category, while the FRAP method has an IC50 value of 72.9311 µg/ml with a strong category. Butterfly leaf extract showed antibacterial efficacy against Streptococcus mutans bacteria at all doses, with maximum inhibition seen at an extract concentration of 50% (inhibition zone diameter: 16.3 mm ± 0.81). The study's findings suggest that butterfly leaf extract works well as a natural antibacterial and antioxidant.